A study of skin characteristics with long‐term sleep restriction in Korean women in their 40s. Issue 2 (6th November 2019) - Jang, Sue Im; Lee, Myeongryeol; Han, Jiyeon; Kim, Jeonghwan; Kim, A Reum; An, Ji Soo; Park, Jin O.; Kim, Beom Joon; Kim, Eunjoo
Abstract: Background: Previous studies have demonstrated increased pore size and darkening skin color with total sleep deprivation. There are many studies of skin characteristics with short‐term sleep restriction, but there are few studies on skin characteristics when sleep is restricted more than three consecutive days. This study evaluated skin changes with sleep limited to 4 hours per night for six nights. Materials and Methods: The study included 32 Korean women in their 40s. Skin hydration, desquamation, barrier recovery, texture, gloss, transparency, elasticity, crow's feet, frown lines, and color were measured. Individual sleep time was monitored by smartwatches. Subjects slept 8 hours per night for six nights in week one and 4 hours per night for six nights in week two. Results: Skin hydration was significantly reduced after 1 day of sleep deprivation, and it continued to decrease. Skin gloss, desquamation, transparency, elasticity, and wrinkles were significantly aggravated after 1 day of sleep deprivation. Skin texture was significantly aggravated on the fourth day of sleep restriction. Elasticity was most affected by reduced sleep, with a standardized coefficient of −.320, indicating a significant decrease over time as compared to other characteristics. Conclusion: Skin hydration was gradually decreased with sleep restriction. Skin texture did not change after only 1 day of sleep restriction. It is a new finding that elasticity decreases more than other skin characteristics with prolonged sleep restriction.